Feminism and LGBTQI+ Rights in Catholic Scout Youth Movement: Navigating among Identities - Ghigi, Rossella; Rolandi, Martina; Tuorto, Dario (SocietàMutamentoPolitica, 2025)
In this paper we examine the advancement of feminist and pro-LGBTQI+ ideals within the Italian Scout movement. This context provides a unique lens to test the interplay between traditional religious frameworks and progressive gender and sexuality discourses, particularly among youth, so contributing to the ongoing exploration of how spaces of youth participation are shaped by gender cultures, and how feminist and LGBTQI+ perspectives can coexist or challenge religious activism. We present data from an original study conducted on four hundreds of scout leaders during a national gathering. Our questionnaire investigates how feminist values and attitudes toward LGBTQI+ rights are embraced by the movement and how these views translate into a distancing from the highly binary rules of scouting and the willingness to change them. We then present a four categories typology of catholic young activists based on their attitudes toward feminism and LGBTQI+ and their religious participation. While girls are more open to addressing these topics, boys feel less comfortable challenging longstanding norms around gender segregation and sexuality. In other words, girls are more likely to show a Secularized or Devoted resistant profile than their male counterparts, who are more likely to be Traditionalist or Detached. Our multivariate models on the likelihood to embrace feminist and LGBTQI+ values emphasize the intersectional nature of factors influencing openness to feminism and LGBTQI+ rights, especially gender and age.